Relationship on economic and attitude factors towards evasion on zakat of income: a study among public servants in Melaka / Zunaidah Ab. Hasan … [et al.] - Ab. Hasan, Zunaidah; Mohd Noor, Abd Halim; Othman, Azhana; Mohd Rafien, Nor Shahrina (Division of Research, Industrial Linkages and Alumni, UiTM Cawangan Melaka, 2011)
This study examines the relationship of economic and attitude factors towards evasion on zakat of income by public servants in Melaka. Past research only focused on factors influencing compliance of payment zakat of income and because the study of zakat payment evasion is very little, this study concentrated in the relationship on economic and attitude factor towards evasion of zakat income among public servants in Melaka. The data was collected through distribution of questionnaire to 254 public servants in Melaka. The objective of the study is to examine the relationship of economic factors and attitude factor towards evasion of payment zakat among public servants. The findings show that there is a positive relationship between economic and attitude factors towards evasion on zakat of income. Implication of this study is to improve the government policy of zakat centre in giving awareness to public servants to pay zakat of income.